PERAN KOMUNIKASI DALAM KELUARGA UNTUK MEMBENTUK SIKAP SOSIAL SISWA DI MTs NURUL YAQIN DESA TELUK KABUNG KECEMATAN GAUNG KABUPATEN INDRAGIRI HILIR - Hermanto Hermanto; Zulhaini Zulhaini; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Etymologically or according to the origin of the said communication, the term comes from the latin, i.e. communication, the root is comunis, but not the party comunis in political activities. the meaning here is the same comunis, within the meaning of the words of the same meaning, that the same meaning of a thing. In the observation that researchers did in MTs Nurul Yaqin Kabung Bay Village find symptoms – symptoms related to the role of communication in the family to form the social attitude of students in mts nurul yaqin kabung Bay Village as follows: 1. The role of the Family in shaping Communications social attitudes have not been created properly, because it still has not been effective communication within the family. 2. Less good communication within the family of social attitudes so that students in schools do not happen with good anyway. 3. communication does not occur between the two directions that form the attitude of openness, so that students in schools do not have social attitudes and openness is good.The author uses data collection techniques in the form of observation, and interviews. As for this kind of research using this type of qualitative research diskriftif, steps-steps Research comprises the study of the findings of the research products that will be developed, developing products, doing field trials in accordance with the the setting in which these products will be used. and techniques of data analysis using quantitative analysis deskriptip be found.The role of communication in the family to form the social attitude of students in MTs Nurul Yaqin Kabung Bay Village Sub District of Indragiri Hilir Echoes. Plays very good in communicating in a family which the family acted as mentors and role models for her children in the family, as well as the social attitude of students in this school is very good, in view of the students behave manners, friendly and caring about each other. Kata Kunci : Peran Komunikasi, Dan Sikap Sosial Siswa